A single strategy: Southeastern Massachusetts Technological Institute by Paul Rudolph - Domingo-Calabuig, Débora (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
Paul Rudolph worked at the Southeastern Massachusetts Technological Institute from 1963 to 1991. Despite not being one of his most popular designs at that time, recent publications have revalued this work by evidencing the coherence between thought and design in a case of large-scale construction. This new campus allowed Rudolph to conceive an 'open work' that ranged from its urban planning to its construction. Other new universities addressed this way of proceeding, but Rudolph was a pioneer in his land in the approach of a design system based on a unique strategy. Thanks to documentary sources of earlier research, this work graphically reconstructs the Arts and Humanities building, the first group to be built and considered the germ of the project. The compositional pattern and the use of a prefabricated concrete block are revealed as basic tools which allow the design flexibility. In the Southeastern Massachusetts Technological Institute, Rudolph focused his attention on the design process under the belief that it would become a product itself, thus joining the ideology of the third-generation architects.
Keywords: Paul Rudolph; Southeastern Massachusetts Technological Institute; Third Generation; campus planning; new university